Directive Speech Acts in Muslim Eid and Christian Easter Sermons: A Syntactic and Pragmatic Study - Mahdi, Athraa' Ammar; Dawood, Mahmood A. (Al-Adab Journal, 2022)
The utterances produced by people have speech acts, especially in the English teaching learning process. One of them is directive speech acts. The main aim of the study is to ascertain contrastively, in English and Arabic, how directive speech acts are represented in religious discourse and what the underlying syntactic structure. For the purpose of the investigation, the directive speech acts of two sermons, one in English and another in Arabic, were extracted and analyzed. A classification taxonomy, was created in order to categorize the different types of directive speech acts and determine their level of (in) directness depending on Bach and Harnish's types of the directive speech acts (1979), The results show that that directive speech acts have the highest occurrences of frequency in Arabic sermon than that in English sermon, since that Islamic sermons belong to the teachings of the Islamic religion which have to be applied the guidelines literally and without ambiguity. Also, Both Arabic and English selected sermons have the highest rate in the form of directness over indirectness in directive speech acts as the speaker wants to send his/her utterances and expressions clearly and without any confusion.